Lipoprotein(a) and Venous Thromboembolism: Association, Causality, and Medications - Pfeferman, Mariana B.; Rashedi, Sina; Lip, Gregory Y. H.; Weber, Christian; O'Donoghue, Michelle L.; Nissen, Steven; Nicholls, Stephen J.; Natarajan, Pradeep; Plutzky, Jorge; Libby, Peter; Goldhaber, Samuel Z.; Piazza, Gregory; Bikdeli, Behnood (Thrombosis and Haemostasis, 2025)
Lipoprotein(a) [Lp(a)] is a circulating plasma lipoprotein with structural similarities to low-density lipoprotein (LDL), distinguished by the addition of apolipoprotein(a) to the LDL structure. Lp(a) levels are approximately 80% genetically determined, and distinct components of this complex particle are thought to confer atherogenic, inflammatory, and antifibrinolytic properties contributing to cardiovascular risk. A growing body of evidence has shown a causal association between elevated Lp(a) levels and both atherosclerotic cardiovascular disease (ASCVD) and valvular aortic stenosis. However, the link with venous thromboembolism (VTE) (encompassing deep vein thrombosis [DVT] and pulmonary embolism [PE]) has been less clear. Although in vitro studies suggest antifibrinolytic and prothrombotic properties for Lp(a), clinical and genetic studies have yielded inconsistent results related to thrombogenicity, with some studies suggesting an association with VTE only with very high Lp(a) levels. The effect of Lp(a) levels on outcomes in patients with incident VTE has not been comprehensively investigated. Although there are currently no approved therapies specifically targeting Lp(a) reduction, at least five agents are in development, with preliminary data demonstrating reductions in Lp(a) levels of up to 98%. The impact of these therapies on VTE events remains unknown. In turn, other lipid-modifying agents, which have no effect on reducing Lp(a), such as statins, were shown to reduce incident VTE. This review summarizes the current evidence regarding the association between Lp(a) and VTE, focusing on its pathophysiology and critically analyzing the existing evidence from experimental, epidemiological, and genetic studies.
Keywords: lipoprotein(a); apolipoprotein(a); venous thromboembolism; deep vein thrombosis; pulmonary embolism; thrombosis